The Dipeptidyl Peptidase Family, Prolyl Oligopeptidase and Prolyl Carboxypeptidase in the Immune System and Inflammatory Disease, including Atherosclerosis - Waumans, Yannick; Baerts, Lesley; Kehoe, Kaat; Lambeir, Anne-Marie; De Meester, Ingrid (Frontiers in Immunology, 2015)
Research from over the past 20 years has implicated dipeptidyl peptidase (DPP) IV and its family members in many processes and different pathologies of the immune system. Most research has been focused on either DPPIV or just a few of its family members. It is however essential to consider the entire DPP family when discussing any one of its members. There is a substantial overlap between family members in their substrate specificity, inhibitors and functions. In this review, we provide a comprehensive discussion on the role of prolyl-specific peptidases DPPIV, FAP, DPP8, DPP9, DPPII, PRCP and PREP in the immune system and its diseases.We highlight possible therapeutic targets for the prevention and treatment of atherosclerosis, a condition which lies at the frontier between inflammation and cardiovascular disease.